Tropical tanniniferous legumes used as an option to mitigate sheep enteric methane emission - Moreira, Guilherme Dias; Tavares Lima, Paulo de Mello; Borges, Barbara Oliveira [UNESP]; Primavesi, Odo; Longo, Cibele; McManus, Concepta; Abdalla, Adibe; Louvandini, Helder (Springer, 2013)
This study presents the first results from Brazil using SF6 tracer technique adapted from cattle to evaluate the capability of condensed tannin (CT) present in three tropical legume forages, Leucaena leucocephala (LEU), Styzolobium aterrimum (STA), and Mimosa caesalpiniaefolia Benth (MIM) to reduce enteric CH4 production in Santa Ins sheep. Twelve male lambs [27.88 +/- 2.85 kg body weight (BW)] were allocated in individual metabolic cages for 20-day adaptation followed by 6 days for measuring dry matter intake (DMI) and CH4 emission. All lambs received water, mineral supplement, and Cynodon dactylon v. coast-cross hay ad libitum. The treatments consisted of soybean meal (710 g/kg) and ground corn (290 g/kg) [control (CON)]; soybean meal (150 g/kg), ground corn (30 g/kg), and Leucaena hay (820 g/kg) (LEU); soybean meal (160 g/kg), ground corn (150 g/kg), and Mucuna hay (690 g/kg) (STA); and soybean meal (280 g/kg), ground corn (190 g/kg), and Mimosa hay (530 g/kg) (MIM); all calculated to provide 40 g/kg CT (except for CON). DMI (in grams of DMI per kilogram BW per day) was lower for LEU (22.0) than CON (29.3), STA (31.2), and MIM (31.6). The LEU group showed emission of 7.8 g CH4/day, significantly lower than CON (10.5 g CH4/day), STA (10.4 g CH4/day), and MIM (11.3 g CH4/day). However, when the CH4 emission per DMI was considered, there were no significant differences among treatments (0.37, 0.36, 0.33, and 0.35 g CH4/g DMI/kg BW/day, respectively, for CON, LEU, STA, and MIM). The sheep receiving STA had shown a tendency (p = 0.15) to reduce methane emission when compared to the CON group. Therefore, it is suggested that tropical tanniniferous legumes may have potential to reduce CH4 emission in sheep, but more research is warranted to confirm these results.
Keywords: Condensed tannin; Leucaena; Mimosa; Mucuna; Santa Ines; SF6 technique